2023
DOI: 10.3389/fonc.2023.1136376
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of sarcopenia on postoperative ICU admission and length of stay after hepatic resection for Klatskin tumor

Abstract: BackgroundHepatic resection of Klatskin tumors usually requires postoperative intensive care unit (ICU) admission because of its high morbidity and mortality. Identifying surgical patients who will benefit most from ICU admission is important because of scarce resources but remains difficult. Sarcopenia is characterised by the loss of skeletal muscle mass and is associated with poor surgical outcomes.MethodsWe retrospectively analysed th.e relationship between preoperative sarcopenia and postoperative ICU admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
4
1
Order By: Relevance
“…Patients with pCCA are particularly susceptible to obstructive jaundice, which can also contribute to inadequate intake and reduced physical activity, thereby inducing sarcopenia 28 . Sarcopenia has been identified as a significant risk factor for poor perioperative outcomes undergoing hepatectomy within 90 days in previous studies, further supporting our findings as we have observed a strong association between sarcopenia and severe postoperative complications 29 . Interestingly, previous studies have also shown that sarcopenia does not appear to be associated with postoperative complications in patients with pCCA, likely due to the limited sample size of the previous studies 7,10 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Patients with pCCA are particularly susceptible to obstructive jaundice, which can also contribute to inadequate intake and reduced physical activity, thereby inducing sarcopenia 28 . Sarcopenia has been identified as a significant risk factor for poor perioperative outcomes undergoing hepatectomy within 90 days in previous studies, further supporting our findings as we have observed a strong association between sarcopenia and severe postoperative complications 29 . Interestingly, previous studies have also shown that sarcopenia does not appear to be associated with postoperative complications in patients with pCCA, likely due to the limited sample size of the previous studies 7,10 …”
Section: Discussionsupporting
confidence: 90%
“…28 Sarcopenia has been identified as a significant risk factor for poor perioperative outcomes undergoing hepatectomy within 90 days in previous studies, further supporting our findings as we have observed a strong association between sarcopenia and severe postoperative complications. 29 Interestingly, previous studies have also shown that sarcopenia does not appear to be associated with postoperative complications in patients with pCCA, likely due to the limited sample size of the previous studies. 7,10 Myosteatosis is a pathological condition characterized by the accumulation of fat within muscle tissue, leading to impaired muscle and mitochondrial function.…”
Section: Multivariate Analysismentioning
confidence: 87%
See 1 more Smart Citation
“…The relatively low disease severity in our study population could explain this discrepancy with previous studies. While 61.8% of the patients were admitted to the ICU immediately after hepatic resection in a previous study [ 33 ], none were admitted to the ICU immediately after PPPD in our study.…”
Section: Discussionmentioning
confidence: 65%
“…In previous meta-analyses evaluating gastrointestinal cancer surgeries [ 31 ] and urologic cancer surgeries [ 32 ], preoperative sarcopenia increased the risk of major complications and was an independent prognostic factor for short survival and increased mortality after surgery. In a previous study evaluating hepatic resection for Klatskin tumors conducted at our institution [ 33 ], preoperative sarcopenia was associated with postoperative ICU admission, length of ICU stay, postoperative complication rate, and in-hospital mortality. In contrast, we found no association between preoperative sarcopenia and postoperative complications or mortality.…”
Section: Discussionmentioning
confidence: 99%